Public Health Insurance, Program Take-Up, and Child Health - Aizer, Anna (The Review of Economics and Statistics, 2007)
Of the ten million uninsured children in 1996, nearly half were eligible for public health insurance (Medicaid) but not enrolled. In response, policy efforts to reduce the uninsured have shifted from expanding Medicaid eligibility to increasing take-up among those eligible. However, little is known about the reasons poor families fail to enroll or the consequences. Using a unique data set I find that information and administrative costs are important barriers to enrollment, especially for Hispanics and Asians. In addition, enrolling children in Medicaid before they get sick promotes the use of preventative care, reduces the need for hospitalization, and improves health.